comparative analysis of seed and cone characteristics and seed-dispersal strategies of three pines in the subsection Sabinianae - Johnson, M; Vander Wall, S.B; Borchert, M (Plant ecology, 2003)
The seed-dispersal systems of Coulter pine (Pinus coulteri), gray pine (P. sabiniana), and Torrey pine (P. torreyana), all of the subsection Sabinianae, are not well understood. These pines occur in arid and semi-arid foothills and mountains of California that are subjected to frequent fires. Cone and seed traits of these three California pines are compared to those of four species of pines (sugar pine, P. lambertiana; Jeffrey pine, P. jeffreyi; ponderosa pine, P. ponderosa; and lodgepole pine, P. contorta) that occur in more mesic environments in the nearby Sierra Nevada mountains. The cones of the Sabinianae pines are large with thick, dense scales, and the scales of gray and Coulter pines are armed with sharp, recurved spines. The seeds of all three species are large, and those of gray and Torrey pines are nearly wingless. In contrast, the Sierra Nevada pines have small to medium-sized seeds with large wings that are initially dispersed by the wind. Heavy wing loading of the Sabinianae pine seeds causes them to fall rapidly, and they are not dispersed far by wind. However, animals remove the fallen seeds rapidly, and rodents and jays scatter hoarded many seeds in the soil. This caching activity results in seedling establishment. The unusual morphology of the cones and seeds of the Sabinianae pines is interpreted as a combination of traits that attract animal dispersers, thwart the foraging activities of seed predators, and promote the survival of seeds in an environment subject to frequent fires.